PENGARUH PENGGUNAAN BUAH NANGKA TERHADAP KUALITAS ES KRIM SUSU KEDELAI - Islamy, Fadhla Nur; Syarif, Wirnelis; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research was motivated by the lack of utilization of soy milk in variety of foodsbecause it has a less favorable flavour, whereas soy milk has high nutritional contentand can be processed into variaty of foods, such as ice cream. The purpose of thisstudy was to analyze the effect of the used of jackfruit as much as 50 gr, 100 gr and150 gr to the quality of color, aroma, texture and taste of soy milk ice cream. Thetype of research was purely experimental with a completely randomized designmethod. The data used were primary data sourced from 30 semi-trained panelists byproposed the organoleptic test format. Analyze data used ANAVA, if Fcount > Ftablethen continued with Duncan test. The result of this research showed that there was asignificant influence from the used of jackfruit to the quality of soy milk ice cream,and the used of fruit jackfruit as much as 150 gr has the best quality soy milk icecream, included: color (white-yellow), aroma (jackfruit),texture (smooth), texture(not crystallized), taste (sweet) and taste (jackfruit).Keywords: Soy Milk, Jackfruit Fruit, Ice Cream, Quality